(untitled) (Journal of Laboratory Animal Science, 2024)
Now-a-days, rapid detection and identification of rodent pathogens such as bacteria, fungi, virus etc., have become important step in the development of therapeutic management of infectious disease. Conventional microbiological diagnostic methods have made inconclusive results in early diagnosis of pathogens as well as demanding labor too. Numerous recent innovations bought us different molecular diagnostics methods aiming to automated laboratory system with rapid detection and identification of rodent pathogens. Those innovative methods targets specific nucleic acid (DNA or RNA) for the detection of microorganisms based on nucleic acid probe (TaqMan chemistry) and amplification chemistry. The present review emphasised on the application of TaqMan chemistry in the design, development and evaluation of commercial kit for rapid detection of rodent pathogens.